2023
DOI: 10.1111/joor.13514
|View full text |Cite
|
Sign up to set email alerts
|

Research routes on awake bruxism metrics: Implications of the updated bruxism definition and evaluation strategies

Abstract: BackgroundWith time, due to the poor knowledge on it epidemiology, the need to focus on awake bruxism as a complement of sleep studies emerged.ObjectiveIn line with a similar recent proposal for sleep bruxism (SB), defining clinically oriented research routes to implement knowledge on awake bruxism (AB) metrics is important for an enhanced comprehension of the full bruxism spectrum, that is better assessment and more efficient management.MethodsWe summarised current strategies for AB assessment and proposed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 133 publications
0
2
0
Order By: Relevance
“…In parallel, recent studies investigating subjective measurements of awake bruxism using questionnaires have reported a prevalence of self-reported awake bruxism of around 30% [1]. In a systematic review [22], the prevalence rates of "possible" awake bruxism were reported to be 32.08% and 16.16% in convenience and population-based samples, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In parallel, recent studies investigating subjective measurements of awake bruxism using questionnaires have reported a prevalence of self-reported awake bruxism of around 30% [1]. In a systematic review [22], the prevalence rates of "possible" awake bruxism were reported to be 32.08% and 16.16% in convenience and population-based samples, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have investigated the prevalence of awake bruxism using questionnaires and real-time self-reports about awake bruxism via a smartphone application. Bracci et al conducted a questionnaire survey to investigate the prevalence of awake bruxism and found that the prevalence of self-reported awake bruxism was as high as 30% across populations [1]. Using a real-time self-report smartphone application, Stanisic et al reported a significant difference in the frequency of awake bruxism between young adults and parents, and a moderate correlation between awake bruxism and stress [2].…”
Section: Introductionmentioning
confidence: 99%